Fibroblast growth factor receptor 2 (FGFR2) fusions in Japanese patients with intrahepatic cholangiocarcinoma. (3rd April 2021) - Tsujie, Masanori; Iwai, Tomohisa; Kubo, Shoji; Ura, Takashi; Hatano, Etsuro; Sakai, Daisuke; Takeda, Yutaka; Kaibori, Masaki; Kobayashi, Tomoe; Katanuma, Akio; Katayose, Yu; Fukase, Koji
Abstract: Objective: Fibroblast growth factor receptor gene alterations have emerged as promising drug targets for intrahepatic cholangiocarcinoma, a rare cancer that has a poor prognosis. This study evaluated the frequency of fibroblast growth factor receptor 2 fusions in clinical specimens from Japanese patients with iCCA. Methods: This study enrolled 116 patients who had histologically or cytologically confirmed adenocarcinoma and been diagnosed as relapsing after resection or with unresectable intrahepatic cholangiocarcinoma. We evaluated the frequency of fibroblast growth factor receptor 2 fusions-positive cells in their specimens using break-apart fluorescent in situ hybridization 'for 114 patients who met the study protocol'. Results: Of a total of 114 cases, six (5.3%) were identified as fibroblast growth factor receptor 2 fusions-positive with a high frequency (87% or more) of fibroblast growth factor receptor 2 fusions-positive tumour cells whereas the remainder, with the exception of three cases with indeterminate results, were identified as fibroblast growth factor receptor 2 fusions-negative. The patients' baseline characteristics as well as their objective response rates, disease control rates, times to progression, and times to treatment failure with previous or ongoing first-line chemotherapy did not have any obvious relationship to the proportion of fibroblast growth factor receptor 2 fusions-positive case. Conclusions: Further detailed elucidation of fibroblast growth factor receptor 2 fusion status is expected to contribute to the development of promising therapeutic options for patients suffering from recurrent or unresectable intrahepatic cholangiocarcinoma. Abstract : A multicenter study on the frequency of fibroblast growth factor receptor 2 fusions-positive tumour specimens in Japanese patients with recurrent or unresectable intrahepatic cholangiocarcinoma.